Training intensity and sagittal curvature of the spine in male and female artistic gymnasts - Sanz-Mengibar, J. M.; Sainz-de-Baranda, P.; Santonja-Medina, F. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Specific adaptations of the spine in the sagittal plane have been described according to different sports disciplines. The goal of this study was to describe the integrative diagnosis of the sagittal morphotype of the spine in male and female artistic gymnasts.